PEMANFAATAN LIMBAH KAYU JABON DAN LIMBAH SERAT SAWIT SEBAGAI BAHAN BAKU BRIKET ARANG - Gultom, Ronny Noprianus; Sulaeman, Rudianda; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The necessaries of energy and fuel in Indonesia will be increase every year due to the increasing of development and population growth. The government encourages people to do energy savings and looking for the alternative of energy resources. One of the alternative energy is biomass energy, biomass can be processed and used as an alternative fuel, for example in the form of charcoal briquettes. This research aims to determine the characteristics of charcoal briquettes from the blend of the jabon wood waste and the palm fiber waste. This research used completely randomized design method which consists of 5 treatments and 3 repetitions. The result showed that the waste of jabon wood and the waste of palm fiber can be used as raw material for charcoal briquettes. The average of water content was 4,28% - 4,76% and the average value of calorific was 5016,48 cal/gram – 6785,68 cal/gram, all treatments are compliance with SNI criteria. The calculation of fuel power does not have the provision of SNI yet, in this research has been obtained an average computation of power fueled by 0,234 gram/minute – 0,308 gram/minute. Keywords: Briquettes, Charcoal, Biomass, Waste